Assessing the impact of varying irrigation levels and biochar applications on bell pepper (Capsicum annuum L.) using remote sensing technology - Jirapat Suksomboon; Himanshu, Sushil Kumar; Datta, Avishek; Yaseen, Muhammad; Her Majesty the Queen{u2019}s Scholarship (Thailand); AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Drought stress can reduce plant growth, development, and yield losses, also affect the bell pepper (Capsicum annuum L.) cultivation. Biochar has been reported to enhance soil water retention and porosity, thereby offering potential resilience under water limited conditions. In parallel, advancements in precision agriculture- particularly the use of thermal imaging, enable non-invasive monitoring of crop water status. This study aimed to evaluate the combined effects of varying irrigation levels and biochar application rates on the growth, physiological responses, yield, and water productivity of bell pepper, while also exploring the potential of remote sensing tools for crop water stress assessment. A factorial greenhouse experiment was conducted using a completely randomized design. The experiment was divided into two factors of four irrigation levels (40, 60, 80, 100% at FC), and four biochar applications (0, 10, 20, 30 t ha-1) Results showed that biochar application significantly improved plant growth parameters, with increases in plant height and stem diameter by approximately 45{u2013}50% and 30{u2013}40%, respectively, compared to the control. Root dry matter increased by 124% under the highest biochar rate (30 t hap-1(B) relative to no biochar. Biochar also positively influenced physiological indicators, while NDVI increased proportionally with irrigation level. Interestingly, under deficit irrigation, total leaf phenolic and flavonoid contents increased, but were suppressed in biochar-amended treatments. The highest fruit yield (359 g plantp-1(B) and water productivity (15.12 kg mp-3(B) were observed under full irrigation (100% FC) with 30 t hap-1 (Bbiochar. However, the treatment with 80% FC and 30 t hap-1 (Bbiochar yielded a comparable water productivity (13.6 kg mp-3(B), suggesting a potential 20% water savings without a substantial yield loss. While fruit pH showed no consistent trend, total soluble solids were lowest under minimal biochar input. Remote sensing-based canopy temperature measurements were used to compute the Crop Water Stress Index (CWSI), which ranged from 0.4 to 0.55 under severe water stress and approached zero for 100% FC. Biochar applications consistently reduce canopy temperature, reflecting its role in mitigating water stress. s
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Bell pepper -- Effect of stress on; Bell pepper -- Remote sensing; Water-supply, Agricultural